SOSIALISASI PEMANFAATAN LIMBAH ORGANIK SEBAGAI SOLUSI PERTANIAN SIRKULAR DI PESANTREN AN-NAJAH CINDAI ALUS PUTRA KABUPATEN TANAH LAUT KALIMANTAN SELATAN - Maulana, Fajri; Febrina, Bunga Putri; Yardani, Jesi; Agasi, Satri Yusasra; Fajri, Fadhli; Yaman, Hafiz Ibnu; Naim, Dimas Amin; Adnan, Muhammad (Jurnal Abdi Insani, 2025)
Unmanaged food waste generated by students and the high cost of agricultural production due to dependence on chemical fertilizers are two major problems faced by Pesantren An-Najah Cindai Alus Putra, Tanah Laut Regency, South Kalimantan. This community service activity aimed to increase the awareness and knowledge of students at Pesantren An-Najah Cindai Alus Putra regarding the use of organic waste as part of a circular agriculture system. Socialization was carried out for 45 students using interactive lectures and educational media, such as PowerPoint presentations, leaflets, and infographics. The materials covered the concept of circular agriculture, the use of food waste as fermented feed for quails, and the utilization of quail feces as raw material for organic fertilizer. Evaluation was conducted through pre-tests and post-tests to assess changes in participants' understanding. The results showed a significant increase in understanding, with an average score improvement of more than 75% in each assessed aspect. These findings demonstrate that contextual and participatory socialization is effective as an initial step in developing an integrated waste management system within the pesantren environment. This activity serves as a vital foundation for the development of sustainable circular agriculture. Going forward, technical training and continuous mentoring are needed to enable pesantren to implement this concept independently and consistently over the long term.